2009
DOI: 10.1039/b819739c
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic mixing under low frequency vibration

Abstract: In the laminar flow regime which characterizes the operation of most microfluidic systems, mixing is governed primarily by molecular diffusion. An increase in the interfacial surface between the fluids contained in the system facilitates the mixing process. This can be obtained by active external perturbation, requiring complex systems and complex operation, or passively by clever design over the geometrical constraints. Here, we describe an active micromixer technique based on the excitation of vortices in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Indeed the correlation of increased mass transfer co-efficient between two fluids given an added LLFV application has been experimentally verified by Hancil et al [31]. Further, Oberti et al, have shown enhanced mixing of particulate laden fluids in articulating channels (analogous to articulating blood vessels) secondary to external LLFV [32,33]. Accordingly, LLFV mixing devices such as produced by Resodyn  Acoustic Mixers (operable at a nominal frequency of 60 Hz) have found common use in industrial mixing of both fluids and solids.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed the correlation of increased mass transfer co-efficient between two fluids given an added LLFV application has been experimentally verified by Hancil et al [31]. Further, Oberti et al, have shown enhanced mixing of particulate laden fluids in articulating channels (analogous to articulating blood vessels) secondary to external LLFV [32,33]. Accordingly, LLFV mixing devices such as produced by Resodyn  Acoustic Mixers (operable at a nominal frequency of 60 Hz) have found common use in industrial mixing of both fluids and solids.…”
Section: Discussionmentioning
confidence: 91%
“…Proposed VC action includes transmission of oscillations from an external body surface to a thrombosed artery to cause mechanical agitation of clot and blood proximate the clot, while also potentially inducing a localized vasodilation response to the culprit vasculature. Turbulence induced at the blood clot interface is predictive (as shown in-vitro ) and inferable (in accordance with hydrodynamic mixing studies [Hancil V et al 1978, Neild A et al 2010, Oberti S et al 2009 ] to encourage systemic mixing of thrombolytics down an otherwise zero flow cerebral artery. Acoustic AIS therapy is generally problematic however as the cerebral arteries are mechanically shielded within the cranium.…”
Section: Introductionmentioning
confidence: 93%
“…A solution to this problem was presented by Oberti et al (2009), andNelid et al (2010). In the work by Oberti et al (2009), the authors showed that mixing can be improved under the low frequency vibration of the whole microchip, whereas, Neild et al (2010), demonstrated a possibility in mixing improvement from low frequency pulsations of the entering fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In the work by Oberti et al (2009), the authors showed that mixing can be improved under the low frequency vibration of the whole microchip, whereas, Neild et al (2010), demonstrated a possibility in mixing improvement from low frequency pulsations of the entering fluid. Similar conclusions can be found in the paper by Glasgow et al (2003) where the numerical analysis showed that mixing in the 2D T-shaped microchip was improved by low frequency (5 Hz) pulsations at one of the inlets.…”
Section: Introductionmentioning
confidence: 99%